Functional Consequences of Monoglucosylation of Ha-Ras at Effector Domain Amino Acid Threonine 35 - Christian Herrmann; Mohammad Reza Ahmadian; Fred Hofmann; Ingo Just (1998)
Monoglucosylation of low molecular mass GTPases is an important post-translational modification by which microbes interfere with eukaryotic cell signaling. Ha-Ras is monoglucosylated at effector domain amino acid threonine 35 by Clostridium sordellii lethal toxin, resulting in a blockade of the downstream mitogen-activated protein kinase cascade. To understand the molecular consequences of this modification, effects of glucosylation on each step of the GTPase cycle of Ras were analyzed. Whereas nucleotide binding was not significantly altered, intrinsic GTPase activity was markedly decreased, and GTPase stimulation by the GTPase-activating protein p120GAP and neurofibromin NF-1 was completely blocked, caused by failure to bind to glucosylated Ras. Guanine nucleotide exchange factor (Cdc25)-catalyzed GTP loading was decreased, but not completely inhibited. A dominant-negative property of modified Ras to sequester exchange factor was not detectable. However, the crucial step in downstream signaling, Ras-effector coupling, was completely blocked. The K d for the interaction between Ras·GTP and the Ras-binding domain of Raf was 15 nm, whereas glucosylation increased theK d to >1 mm. Because the affinity of Ras·GDP for Raf (K d = 22 μm) is too low to allow functional interaction, a glucose moiety at threonine 35 of Ras seems to block completely the interaction with Raf. The net effect of lethal toxin-catalyzed glucosylation of Ras is the complete blockade of Ras downstream signaling.